2020
DOI: 10.1007/s00405-020-06261-8
|View full text |Cite
|
Sign up to set email alerts
|

Tumor, host and surgery related factors predisposing to cranial nerve deficits after surgical treatment of parapharyngeal space tumors

Abstract: Propose Identification of relevant features acquired on preoperative evaluation of parapharyngeal space (PPS) tumors or related to the performed surgical approach that are predictive of the most important complication of surgical treatment of these tumors, cranial nerve palsy. Methods This was a retrospective analysis of 68 patients with PPS tumors treated with surgical resection in a tertiary referral center from 2009 to 2019. The preoperative clinical symptoms, age, sex, tumor size, location, histopathologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…5 Few of our patients presented with tumors of massive size (10 cm × 12 cm). In Rzepakowskaet al 3 study the majority of tumors 39 (57.4%) were located in the prestyloid space. There were 11 (16.2%) postyloid tumors and the same number of tumors involving both localizations.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…5 Few of our patients presented with tumors of massive size (10 cm × 12 cm). In Rzepakowskaet al 3 study the majority of tumors 39 (57.4%) were located in the prestyloid space. There were 11 (16.2%) postyloid tumors and the same number of tumors involving both localizations.…”
Section: Resultsmentioning
confidence: 91%
“…In current study showed that female was predominate 59.4% and male 40.6%. Rzepakowska et al 3 reported there were 46 (67.6%) women and 22 (32.4%) men with a mean age of 52.2 years (age range 33-92 years). Regarding sign and symptoms the most common symptoms of neurogenic tumors were a neck swelling (100%), sorethroat (34.38%), dysphagia (28.13%) and dysphonia (25.0%) and intraoral mass (18.75%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…14,[25][26][27][28] In addition, the treatment strategy for pleomorphic adenoma or schwannoma, such as approach selection, extracapsular/intracapsular dissection, and surgical-related neurovascular morbidity, is clearly different. 23,24,29 As pattern 1 was closely related to pleomorphic adenoma and pattern 2 to schwannoma, this new classification helps in generating a detailed preoperative plan with regard to the options of approaches, possible complications, and expected outcomes. We consider that the classification of tumors, as we described above, is valuable for planning surgical strategies.…”
Section: Discussionmentioning
confidence: 99%